Influence Of Corporate Governance, Leverage And Financial Performance On Earning Management On Manufacturing Companies On The Indonesia Stock Exchange - Mersiana Varia Juita (Enrichment : Journal of Management, 2021)
The purpose of this study is to find out the strong influence of corporate governance, leverage, and financial performance on earning management. Independent factors in the study were management ownership, institutional ownership, independent commissioners, leverage and financial performance. Bound variables are managerial ownership and institutional ownership. The earnings management variable is used as a bound variable. The businesses included in this study are manufacturing companies in the food and beverage industry listed on the Indonesia Stock Exchange during the period of three years 2017 to 2019. The study used quantitative research techniques, such as purposive sampling, resulting in 24 company samples or 120 research samples. The sample size is determined by a set of criteria, and the sample is taken from a pool of participants. Multiple linear analysis techniques were used in this study. Normality test, multicollinearity test, autorelation test, and the heteroskedasticity test is an example of the classical assumptions used in data analysis. It seems from the finding that managerial ownership has little impact on earning management because share ownership is very insignificant. Earning management is not affected by institutional ownership because institutional ownership relates only to current income and only current income. Independent commissioners have no influence on earnings management. The use of leverage has little impact on profit management. It doesn't matter how well the business is running financially because the company's strong profits show that the company is doing well on the other side of the equation.